General And Special Physical Training. Physical Qualities Required By Table Tennis Players (Global Scientific Review, 2024)
This article presented information on the general and special physical fitness necessary for table tennis practitioners and on the importance of developing these qualities in different ways. Also, important aspects of these preparations are highlighted in the development of the level of physical fitness of table tennis players